2017
DOI: 10.1002/adsc.201700270
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Difluoromethylthiolation, Trifluoromethylthiolation, and Perfluoroalkylthiolation with Sodium Difluoromethane‐ sulfinate, Sodium Trifluoromethanesulfinate or Sodium Perfluoro‐ alkanesulfinate

Abstract: Am ethod for direct difluoromethylthiolation of Ar À Hb onds is introduced. Thes tablea nd easy-to-handleH CF 2 SO 2 Na is reduced with (EtO) 2 P(O)H in the presence of TMSCl to generate HCF 2 S + + for the regioselective difluoromethylthiolation of aromatic compoundsi ncluding indoles, pyrroles,and activatedbenzenes. This method is also applicable for the trifluoromethylthiolationw ith CF 3 SO 2 Na and the perfluoroalkylthiolation with R f SO 2 Na of arenesa nd heteroarenes.R eaction mechanisms associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 95 publications
1
30
0
Order By: Relevance
“…On the basis of the experimental results above and previous reports, [11][12][13][14][15]22] it can be deduced that CF 3 SCl and CF 3 SOCl are formed as key intermediates in the reaction and undergo subsequent trifluoromethylthiolation and trifluoromethylsulfinylation, respectively, with 1. It can be inferred that the formation of 2a versus 3a is a competitive process.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…On the basis of the experimental results above and previous reports, [11][12][13][14][15]22] it can be deduced that CF 3 SCl and CF 3 SOCl are formed as key intermediates in the reaction and undergo subsequent trifluoromethylthiolation and trifluoromethylsulfinylation, respectively, with 1. It can be inferred that the formation of 2a versus 3a is a competitive process.…”
Section: Resultsmentioning
confidence: 61%
“…[12] Sodium trifluoromethanesulfinate (CF 3 SO 2 Na), also known as Langlois reagent, and other sodium perfluoroalkanesulfinates are inexpensive and readily available commercial chemicals. [15] Meanwhile, Cai and co-workers reported a transition-metal-free trifluoromethylthiolation reaction of indole and its derivatives by using a CF 3 SO 2 Na/PPh 3 system and found that an additional X + source such as N-chloro-or N-bromophthalimide was essential for the reaction. [13] In 2015, Zhang et al reported a CuCl-catalyzed trifluoromethylthiolation reaction of indoles by using a CF 3 SO 2 Na/ (EtO) 2 P(O)H system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…of phosphorus oxychloride in N,N-dimethyl formide (DMF) at room temperature in 0.5 hour, 19 F NMR monitoring indicated that trifluoromethylsulfinylation product (3a) was obtained in 89 % yield along with trace amount of trifluoromethylthiolated compound (2a) ( Table 1, entry 1). Other solvents, such as acetonitrile, tetrahydrofuran (THF), 1,4-dioxane, toluene, dimethyl sulfoxide (DMSO) and dimethylamide (DMA), were not suitable for this reaction (entries [14][15][16][17][18][19]. Inspired by this result, we commenced searching for a suitable condition to improve the yield of bifunctionalization product (4a).…”
Section: Resultsmentioning
confidence: 99%
“…[15] As we all know, sodium trifluoromethanesulfinate (CF 3 SO 2 Na, Langlois reagent) is a cheap and easily available commercial chemical. [17] Meanwhile, Cai and co-workers also developed a direct trifluoromethylthiolation of indole derivatives with CF 3 SO 2 Na/PPh 3 system, but an additional X + source such as N-chlorophthalimide was essential for this reaction. [16] And transition-metal-free fluoroalkylthiolation reaction was achieved using a similar reagent system very recently.…”
Section: Introductionmentioning
confidence: 99%